Stem cell labeling for delivery and tracking using noninvasive imaging - Kraitchman, Dara L.; Wu, Joseph Ching-Ming, 1971- (Series in medical physics and biomedical engineering., 2012)
"Stem Cell Labeling for Delivery and Tracking Using Noninvasive Imaging provides a comprehensive overview of cell therapy imaging, ranging from the basic biology of cell therapeutic choices to the preclinical and clinical applications of cell therapy. It emphasizes the use of medical imaging for therapeutic delivery/targeting, cell tracking, and determining therapeutic efficacy. The book first presents background information and insight on the major classes of stem and progenitor cells. It then describes the main imaging modalities and state-of-the-art techniques that are currently employed for stem cell tracking. In the final chapters, leading scholars offer clinical perspectives on existing and potential uses of stem cells as well as the impact of image-guided delivery and tracking in major organ systems. Through clear descriptions and color images, this volume illustrates how noninvasive imaging is used to track stem cells as they repair damaged tissue in the body. With contributions from some of the most prominent preclinical and clinical researchers in the field, the book helps readers to understand the evolving concepts of stem cell labeling and tracking as the field continues to move forward"--Provided by publisher.